2017
DOI: 10.1016/j.canlet.2016.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin anti-tumor mechanisms include Hsp60 post-translational modifications leading to the Hsp60/p53 complex dissociation and instauration of replicative senescence

Abstract: a b s t r a c tThe chaperone Hsp60 is pro-carcinogenic in certain tumor types by interfering with apoptosis and with tumor cell death. In these tumors, it is not yet known whether doxorubicin anti-tumor effects include a blockage of the pro-carcinogenic action of Hsp60. We found a doxorubicin dose-dependent viability reduction in a human lung mucoepidermoid cell line that was paralleled by the appearance of cell senescence markers. Concomitantly, intracellular Hsp60 levels decreased while its acetylation level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…These findings suggest that the reduction of Hsp60 levels might have various causes, as it has been already demonstrated, in which Hsp60 could be tagged by post-translational modifications, such as hyperacetylation and ubiquitination. This could regulate the degradation of the chaperone by the ubiquitin-proteosome system [12,55]. Otherwise, the post-translational modifications could constitute a signal for extracellular secretion through the lipid raft pathway [11,49,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the reduction of Hsp60 levels might have various causes, as it has been already demonstrated, in which Hsp60 could be tagged by post-translational modifications, such as hyperacetylation and ubiquitination. This could regulate the degradation of the chaperone by the ubiquitin-proteosome system [12,55]. Otherwise, the post-translational modifications could constitute a signal for extracellular secretion through the lipid raft pathway [11,49,56].…”
Section: Discussionmentioning
confidence: 99%
“…The function of extracellular Hsp60 is still under discussion. For instance, it may mediate interactions with the immune cells and other body tissues and alter the tumor microenvironment [11,12,55,57].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-scavenging activity of these cultivars was positively correlated with both ascorbic acid and total polyphenol contents [30], albeit the authors did not explore the biochemical mechanism responsible for the observed effects. In this scenario, we recently started to explore the antioxidant and anti-aging properties of Sicilian mango extracts exploiting our knowledge in the study of oxidative stress and cell death induction in tumour systems [31,32,33,34,35,36,37]. Using fruit extract from the Kensington Pride cultivar grown and widely spread in Balestrate (Palermo) and other Sicilian rural areas, our preliminary results provided evidence that exocarp, mesocarp, and endocarp of mango can efficaciously counteract oxidative damage caused by ROS.…”
Section: Antioxidant Properties Of Mangifera Indica Lmentioning
confidence: 99%
“…The treatment with a copper compound with cytotoxic properties induced the decrease in the HSP60 levels, the separation of the complex HSP60/pC3, and consequently, the C3 activation of the caspase pathway associated with a tumor-cell growth arrest [50]. In addition, we found that the antitumor agent doxorubicin acted on the NCI-H292 cell line by lowering the levels of intracellular HSP60 and determining the HSP60 acetylation, which seems to be responsible for the disruption of Hsp60/p53 complex and the activation of replicative senescence, probably via p53-p21 pathway [51]. Our previous findings reported that high levels of HSP60 may have an anti-apoptotic and cytoprotective role in cancer [15,[50][51][52].…”
Section: Discussionmentioning
confidence: 73%